Aggregation Pheromone of Palm Weevil, Dynamis borassi - Peña, Jorge E. (1997)
4-Methyl-5-nonanol (1) is the male-produced aggregation pheromone of the palm weevil, Dynamis borassi (F.) from Colombia. The pheromone was identified by coupled gas chromatographic–electroantennographic detection (GC-EAD) analysis of male- and female-produced volatiles, and comparative GC–mass spectrometry (MS) of weevil-produced 1. In field experiments in Colombia, traps baited with a stereoisomeric mixture of synthetic 1 (3 mg/day) plus sugarcane captured more weevils than traps baited with 1 or sugarcane alone, suggesting that pheromone and plant volatiles are synergistically attractive. Use of a chiral, stereoisomer-separating Cyclodex-B column in GC-EAD and GC-MS analyses revealed that D. borassi males produce, and antennae of males and females respond to (4S,5S)-1. Previously identified palm weevil (Rhynchophorus spp.) aggregation pheromones 5-methyl-4-octanol (cruentol) and 6-methyl-2-hepten-4-ol (rhynchophorol) also elicited antennal responses by D. borassi. In field experiments, D. borassi females were captured equally well in traps baited with sugarcane plus either 1, cruentol or rhynchophorol. In contrast, D. borassi males were captured most often in traps baited with sugarcane plus 1. Because D. borassi is a potential vector of the red ring nematode that causes the lethal red ring disease of palms, pheromone-based trapping of D. borassi could aid in monitoring or management of red ring disease in commercial palm plantations.